The effect of the video assistant referee (VAR) on referees' decisions at FIFA Women's World Cups - Zhang, Yeqin; Li, Danyang; Gómez-Ruano, Miguel-Ángel; Memmert, Daniel; Li, Chunman; Fu, Ming (Frontiers in Psychology, 2022)
Video assistant referee (VAR) has been implemented in women’s football, aiming to improve referees’ decision-making, but its impact has not yet been analyzed. This study intended to explore how the VAR affects refereeing decisions at Fédération Internationale de Football Association (FIFA) Women’s World Cup competitions. The sample includes all 52 matches played in the 2015 tournament before VAR was introduced and all 52 matches played in the 2019 competition where VAR was deployed. For each match, data on ten variables were collected: first half playing time, second half playing time, total playing time, penalties, offsides, fouls, goals, corner kicks, yellow cards, and red cards. The match variables were compared before and after VAR implementation using a Mann–Whitney U test, a Bayesian analysis, a generalized linear model, and a non-clinical magnitude-based inference. The results demonstrated that after VAR was introduced, playing time during the first half (p < 0.001, BF10 = 547.05, Cohen’s d = 1.06, 90%CI [0.71, 1.40]), the second half (p < 0.001, BF10 = 57.09, Cohen’s d = 0.91, 90%CI [0.57, 1.25]), and the entire match (p < 0.001, BF10 = 1120.39, Cohen’s d = 1.33, 90%CI [0.97, 1.69]) increased significantly with moderate to large effect sizes, while the number of penalties, offsides, and fouls did not vary significantly neither did the number of goals, corner kicks, yellow cards, and red cards. This study has practical implications for professionals in terms of a better understanding of VAR’s impact on elite women’s football.